The Presence of Sultan's Grant in Land Determination in Indonesia: a Case Study in Morowali - Weri, Asmadi; Kemala Sari, Dewi; Hiola, Adiguna Kharismawan (Fakultas Hukum Universitas Hang Tuah, 2024)
The study investigates the implementation of the Sultan Bungku grant in Morowali Regency, Indonesia, given its historical significance and potential for land conflicts in the region. This research Purpose of Writing for aims to understand how the Sultan Bungku grant, a traditional land tenure system, has been adapted to contemporary land governance practices in Morowali, especially in light of industrial development. This research method is A normative legal research approach was employed, combined with interviews with relevant stakeholders in Morowali Regency. The study found that while the Sultan Bungku grant has historical significance, its implementation has been influenced by the introduction of modern land tenure systems, such as those established by the National Land Agency (BPN). This has led to a complex interplay between traditional and modern land governance practices. Despite the potential for land conflicts, the presence of the BPN and local government has contributed to a relatively stable investment environment in Morowali. This research provides valuable insights into the evolution of land tenure systems in Indonesia, particularly in regions with historical ties to traditional land governance. It highlights the challenges and opportunities associated with balancing traditional practices with modern land administration.